Crankshaft high cycle bending fatigue research based on the simulation of electromagnetic induction quenching and the mean stress effect. (April 2021) - SongSong, Sun; Xingzhe, Zhang; Chang, Wu; Maosong, Wan; Fengkui, Zhao
Highlights: 3D finite element simulation of the induction hardening process. Comparative study of different mean stress models in crankshaft fatigue research. Combination of the mean stress model and multi-axial fatigue. Abstract: Electromagnetic induction quenching is one of the common surface strengthening approaches conducted engineering application, especially for the steel parts. In this paper, first a 3D finite element model was built and the electromagnetic thermal coupling simulation was used to determine the temperature field after quenching and coolant cooling process. Then the mechanical-thermal coupling simulation was used to obtain the residual stress field remaining in the crankshaft after air cooling. Finally the fatigue property of the treated crankshaft was predicted based on the residual stress and the different mean stress models. Validations between the predictions and the experimental results showed that the combination of the simulation and Goodman model can obtain the fatigue property of this type of crankshaft accurately, thus was suitable for actual engineering applications.